Дисперсійні характеристики гіроелектричних фотонних кристалів - Демиденко, Є. Є.; Новицький, В. В. (ХНУРЕ, 2025)
A two-dimensional model of the photonic crystal with gyrotropic elements is considered. The effect of external magnetic field on the dispersion characteristics of the photonic crystal is numerically investigated. The effect of the external magnetic field on the band diagrams of the photonic crystal shows the change of the frequency band gap parameters. This result points to a possibility of controlled photonic crystal devices being built in microwave, terahertz and optical ranges
Keywords: гіроелектричний фотонний кристал; photonic crystal